1999
DOI: 10.1115/1.555458
|View full text |Cite
|
Sign up to set email alerts
|

Local Swirl Chamber Heat Transfer and Flow Structure at Different Reynolds Numbers

Abstract: Local flow behavior and heat transfer results are presented from two swirl chambers, which model passages used to cool the leading edges of turbine blades in gas turbine engines. Flow results are obtained in an isothermal swirl chamber. Surface Nusselt number distributions are measured in a second swirl chamber (with a constant wall heat flux boundary condition) using infrared thermography in conjunction with thermocouples, energy balances, and in situ calibration procedures. In both cases, Reynolds numbers Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…The oil particles are provided by seeder (LAVision) for velocity measurements. Acrylic also works well for infrared imaging because its surface emissivity ranges from 0.60 to 0.65 [9]. Particle images are taken using two high resolution cameras and processed by DaVis software as shown in Fig.…”
Section: Swirl Flow Using 3-d Stereo-pivmentioning
confidence: 99%
See 2 more Smart Citations
“…The oil particles are provided by seeder (LAVision) for velocity measurements. Acrylic also works well for infrared imaging because its surface emissivity ranges from 0.60 to 0.65 [9]. Particle images are taken using two high resolution cameras and processed by DaVis software as shown in Fig.…”
Section: Swirl Flow Using 3-d Stereo-pivmentioning
confidence: 99%
“…All three Re numbers (nominal and ±50%) are presented at Re = 7,000, 14,000, and 21,000 and flow rate measurements were plotted for all velocity profiles involving the TLC experiment. The definition of the swirl number is the ratio of the flux of angular momentum and the flux of axial momentum per Moon, et al [1] and Hedlund, et al [9]. Fig.…”
Section: Swirl Number Magnitudesmentioning
confidence: 99%
See 1 more Smart Citation
“…The swirling flow can also be influenced by the air inlet geometry [5]. Hedlund et al [6][7] reviewed a variety of devices and geometries to produce swirl in internal flows. They studied another swirl chamber which employed tangential jets from wall slots or ducts to produce large scale swirling in internal tube flows.…”
Section: Introductionmentioning
confidence: 99%
“…investigated the flow field in a swirl chamber with tangential injection and found that the reason for the rise in heat transfer is the radial pressure gradient and the high turbulence. There are much more proceedings dealing with this topic, for example Glezer et al [1996] and Hedlund et al [2000] but there is only one known where swirling flow was investigated in a rotating system. This is Glezer et al [1998].…”
mentioning
confidence: 99%